Vitamin D, a modulator of musculoskeletal health in chronic kidney disease. Issue 5 (3rd July 2017) - Molina, Pablo; Carrero, Juan J.; Bover, Jordi; Chauveau, Philippe; Mazzaferro, Sandro; Torres, Pablo Ureña; ,
Abstract: The spectrum of activity of vitamin D goes beyond calcium and bone homeostasis, and growing evidence suggests that vitamin D contributes to maintain musculoskeletal health in healthy subjects as well as in patients with chronic kidney disease (CKD), who display the combination of bone metabolism disorder, muscle wasting, and weakness. Here, we review how vitamin D represents a pathway in which bone and muscle may interact. In vitro studies have confirmed that the vitamin D receptor is present on muscle, describing the mechanisms whereby vitamin D directly affects skeletal muscle. These include genomic and non‐genomic (rapid) effects, regulating cellular differentiation and proliferation. Observational studies have shown that circulating 25‐hydroxyvitamin D levels correlate with the clinical symptoms and muscle morphological changes observed in CKD patients. Vitamin D deficiency has been linked to low bone formation rate and bone mineral density, with an increased risk of skeletal fractures. The impact of low vitamin D status on skeletal muscle may also affect muscle metabolic pathways, including its sensitivity to insulin. Although some interventional studies have shown that vitamin D may improve physical performance and protect against the development of histological and radiological signs of hyperparathyroidism, evidence is still insufficient to draw definitive conclusions.